Edge magnetic island excitation in the U-2M torsatron - Kotenko, V.G.; Moiseenko, V.E. (Вопросы атомной науки и техники, 2016)
In the article, via numerical calculations a possibility of magnetic island structure excitation on the edge of closed
magnetic surface configuration in a torsatron with the additional toroidal magnetic field coils is shown. The applied
scheme to realize the structure is founded on a particular shunting of electrical current in one of the coils. The
calculations were carried out taking into account the geometry of the torsatron U-2M functional magnetic system. C помощью численных расчётов показана возможность возбуждения островной структуры на краю
конфигурации магнитных поверхностей в торсатроне с катушками дополнительного тороидального
магнитного поля. Практическая схема реализации структуры основана на частичном шунтировании
электрического тока в одной из этих катушек. Расчёты проведены с учётом геометрии действующей
магнитной системы торсатрона У-2М. За допомогою чисельних розрахунків показана можливість збудження острівної структури на краю
конфігурації магнітних поверхонь у торсатроні з котушками додаткового тороїдального магнітного поля.
Практична схема реалізації структури заснована на частковому шунтуванні електричного струму в одній із
цих котушок. Розрахунки проведені з врахуванням геометрії діючої магнітної системи торсатрона У-2М.